Regional Scale Ecological Risk Assessment: Using the Relative Risk Model - Landis, Wayne (CRC Press, 2009)
Regional Scale Ecological Risk Assessment: Using the Relative Risk Model is a collaborative summary and guidebook of the development, methods, and application of the Relative Risk Model (RRM) to meet the need for regional assessments with multiple stressors from diverse sources and numerous desired endpoints. Amenable to additional iterations as new information becomes available, this assessment model is ideal for designing a dynamic management plan that can be customized to meet specific ecological needs.